Risk factors and one-year mortality in patients with direct oral anticoagulant-associated gastrointestinal bleeding. Issue 208 (December 2021) - Verso, Melina; Giustozzi, Michela; Vinci, Alessandra; Franco, Laura; Vedovati, Maria Cristina; Marchesini, Emanuela; Becattini, Cecilia; Agnelli, Giancarlo
Abstract: Background and aim: Risk factors and mortality in patients with DOACs-associated gastrointestinal bleeding (GIB) are not completely defined. Aims of this study were to identify risk factors for bleeding and evaluate one-year mortality in patients with DOACs-associated GIB. Methods: We conducted a case-control study. Cases were patients with DOACs-associated GIB admitted to the Perugia Hospital, Italy between 2013 and 2019. Controls were derived from the prospective database of patients with DOACs referred to the ambulatory service. Cases and controls were matched by a 1:2 ratio for type and dose of DOAC, indication for anticoagulation and gender. Univariate and multivariable analyses were performed to identify risk factors. Hazard Ratio with 95% confidence interval was used to calculate mortality. Results: We included 324 patients, of which 108 with DOACs-associated GIB. Mean age was 81.9 ± 7.2 years and 78.9 ± 8.7 years, respectively. The most frequent indication for anticoagulation was atrial fibrillation. Reduced doses of DOACs were prescribed in 186 patients (56.4%). At multivariable analysis, active cancer (OR:7.26; 95%CI 3.10–16.96), renal impairment (OR:4.26; 95%CI 1.98–9.17), bleeding predisposition (OR:3.66; 95%CI 2.00–6.68), COPD (OR:2.12; 95%CI 1.08–4.16) and uncontrolled hypertension (OR:1.86; 95%CI 1.07–3.23) were found to be predictors for DOACs-associated GIB. Adjusted one-year mortality was significantly higher in patients who experienced GIB compared with those who did not experience GIB (OR: 7.04; 95%CI 3.82–14.31). Conclusions: Predictors of DOACs-associated GIB included active cancer, renal impairment, bleeding predisposition, COPD and uncontrolled hypertension. The adjusted one-year-mortality was significantly increased in patients with DOACs-associated GIB in comparison to DOACs patients without GIB. Highlights: DOACs have a favorable risk–benefit profile, but the rate of GIB remains clinically relevant. Risk factors and one-year-mortality in patients with DOACs-associated GIB are not completely defined. Cancer, renal impairment, bleeding risk, COPD and uncontrolled hypertension are independent risk factors for DOACs-associated GIB. Adjusted one-year-mortality is increased in patients with DOACs-associated GIB. The identification of predictors for GIB could help to identify high-risk patients for GIB.